ETV4 promotes the progression of cholangiocarcinoma by regulating glycolysis via the TGF-β signaling - Fangfeng Liu; Qianchang Wang; Zhengjian Wang; Shizhe Zhang; Qingqiang Ni; Hong Chang (Translational Oncology, 2024)
Background: Considerable studies show that ETS variant 4 (ETV4) plays an important roles in multitudinous tumor. This study investigated its function in cholangiocarcinoma (CCA) progression and revealed the underlying mechanisms. Methods: The expression of ETV4 in CCA was evaluated using TCGA database and the single-cell analysis based on GSE189903 dataset. ETV4 expression in CCA human specimens was detected by reverse transcription-quantitative PCR, immunohistochemistry, and western blot. Cell Counting Kit-8, EdU, colony formation, wound healing, and Transwell assays were used to analyze the effects of ETV4. Extracellular acidification rate, oxygen consumption rate, glucose uptake, and lactate production were used to measure glycolysis in CAA cells. Western blot was performed to explore glycolysis-related proteins. Tumor growth was evaluated in mice xenograft tumors. Results: ETV4 was up-regulated in CCA epithelial cells. The high-expression of ETV4 was associated with poor prognosis of patients with CCA. ETV4 overexpression enhanced the proliferation, migration, invasion, and glycolysis of CCA cells; ETV4 silencing led to the contrary effects. Mechanistically, ETV4 activates TGF-β/Smad2/3 signaling pathway. In mice xenograft mode, ETV4 silencing inhibits the tumor growth, the expression of glycolysis-related proteins and TGF-β/Smad2/3 pathway proteins. Conclusions: ETV4 functions as an essential factor in the roles of TGF-β1 in CCA cells, and may be a promising target for TGF-β1-mediated CCA progression.